First record of Chloridea (Heliothis) subflexa (Lepidoptera: Noctuidae: Heliothinae) on cape gooseberry (Physalis peruviana) in Brazil (2018)
Chloridea (Heliothis) subflexa (Guenée) (Lepidoptera: Noctuidae: Heliothinae) is a frugivorous and monophagous species with plant hosts in the genus Physalis. In the last few years, the subflexus straw moth became the main pest-insect in tomatillo crops (Physalis ixocarpa Brotero) in Mexico and cape gooseberry (Physalis peruviana L.) crops in Argentina. The objective was to provide the first record of C. subflexa on P. peruviana in Brazil. The specimens were collected in the larval stage and kept on a natural diet until reaching the adult stage. Species identification was carried out based on morphological criteria. Damage from C. subflexa on P. peruviana fruits cultivated in an organic system were recorded. This is the first record in Brazil.